Varieties of Ideology. Reassessing Europe's Open Society and Its Enemies in the Euro Area - Stefan Collignon; Davide Orsitto (London School of Economics and Political Science (LSE), European Institute, 2024)
The coherence of ideological narratives in the Euro Area is a necessary condition for the sustainability of the monetary union. Narratives shape political preferences and if they diverge persistently, cooperation between member states becomes impossible. We measure the evolution of ideological narratives in member states of the Euro Area over half a century in a two-dimensional space. In addition to the classical right-left cleavage, we define a cultural dimension that is inspired by Karl Popper's and Dumont's distinction between individualism and holism, i.e., between open and closed societies. We find that ideological preferences, as expressed by people voting for party programs, have converged - but less so in the new member states. Thus, the institutional framework of the monetary union has contributed to greater ideological convergence inside the Euro Area while it is significantly weaker outside the Euro Area. However, since the end of the Cold War, most societies have become less open which makes cooperation between ideologically closed society more difficult. Germany is the leader of a conservative group of member states, France of a progressive group. Both models are compatible with the Maastricht objectives of price stability and low public debt ratios, but only the French model of open society with social equality supports economic growth.
Keywords: 330; Ideology; Euro Area; individualism; holism; right-left cleavage; preference convergence; economic growth; inflation; public debt